2022
DOI: 10.3389/fncel.2022.956079
|View full text |Cite
|
Sign up to set email alerts
|

Microglial activation in the motor cortex mediated NLRP3-related neuroinflammation and neuronal damage following spinal cord injury

Abstract: Spinal cord injury (SCI) is a traumatic event that can lead to neurodegeneration. Neuronal damage in the primary motor cortex (M1) can hinder motor function recovery after SCI. However, the exact mechanisms involved in neuronal damage after SCI remain incompletely understood. In this study, we found that microglia were activated in M1 after SCI, which triggered Nod-like receptor protein 3 (NLRP3) related chronic neuroinflammation and neuronal damage in vivo. Meanwhile, treatment with the microglia inhibitor mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…demonstrated that NLRP3-related inflammation in motor neurons was induced by microglial activation in the motor cortex, which impaired motor function recovery after SCI. Minocycline inhibited microglia activation, thus reducing NLRP3-related inflammation and promoting functional recovery after SCI ( 53 ). More recently, an increasing number of chemicals and molecules, such as trehalose ( 54 ), cannabinoid receptor-2 ( 55 ), zinc ( 56 ), melatonin ( 57 ), and dopamine ( 58 ), have been found to improve functional recovery after SCI by targeting NLRP3 inflammasome directly or indirectly.…”
Section: Inflammasomes Are Involved In Inflammation and Immune Respon...mentioning
confidence: 99%
See 2 more Smart Citations
“…demonstrated that NLRP3-related inflammation in motor neurons was induced by microglial activation in the motor cortex, which impaired motor function recovery after SCI. Minocycline inhibited microglia activation, thus reducing NLRP3-related inflammation and promoting functional recovery after SCI ( 53 ). More recently, an increasing number of chemicals and molecules, such as trehalose ( 54 ), cannabinoid receptor-2 ( 55 ), zinc ( 56 ), melatonin ( 57 ), and dopamine ( 58 ), have been found to improve functional recovery after SCI by targeting NLRP3 inflammasome directly or indirectly.…”
Section: Inflammasomes Are Involved In Inflammation and Immune Respon...mentioning
confidence: 99%
“…Hu et al. demonstrated that microglial activation triggered NLRP3-related inflammation in the motor cortex after SCI ( 53 ). Liu et al.…”
Section: Inflammasomes Are Involved In Inflammation and Immune Respon...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ASC is predominantly expressed in microglia following SCI . Moreover, the activation of microglia in the motor cortex has been correlated with NLRP3-mediated neuroinflammation and neuronal degeneration subsequent to SCI . Following the onset of SCI, astrocytes infiltrate the damaged tissue, release inflammatory mediators, and contribute to the development of fibrosis .…”
Section: Inflammatory Responses In Post-sci Mood Disorders: Role Of N...mentioning
confidence: 99%
“…79 Moreover, the activation of microglia in the motor cortex has been correlated with NLRP3-mediated neuroinflammation and neuronal degeneration subsequent to SCI. 156 Following the onset of SCI, astrocytes infiltrate the damaged tissue, release inflammatory mediators, and contribute to the development of fibrosis. 157 The progression of secondary damage in the spinal cord is significantly influenced by the activation of ASC-dependent inflammasomes, specifically in resident cells such as astrocytes and microgelia.…”
Section: Disorders: Role Of Nlrp3 Inflammasomementioning
confidence: 99%